Menumbuhkan Sikap Bangga Berbahasa Indonesia Melalui Pengenalan Bahasa dalam Kegiatan Sehari-Hari - Karisa Zahfa Trimulia; Tasya Nursakinah Ruhiati (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
Indonesian is a national identity that every citizen should be proud of. However, the challenges of globalization and the influence of foreign cultures often weaken the sense of pride in the use of Indonesian in everyday life. The purpose of this article is to describe an effort to foster a sense of pride in Indonesian by introducing it into everyday life. This approach involves incorporating Indonesian into various activities. Through the habituation of using Bahasa Indonesia appropriately and accurately, individuals can understand the richness of culture and its role in strengthening national unity. The results show that individuals' direct involvement in language practice increases awareness of the importance of language as a medium of communication that reflects national values.